THE FULFILLMENT OF ECONOMIC RIGHTS IN SPOTIFY - Cloudio Ardelle Hitipeuw; Fajar Sugianto (International Journal of Law in Changing World)
People no longer enjoy music through CDs, VCDs, and the like. People prefer to enjoy music through digital streaming platforms such as Spotify, making it easy for them to enjoy all the songs available, anytime and anywhere. However, this technological advancement does not necessarily protect creators’ and copyright holders’ rights to royalties. Therefore, the law must evolve to protect creators and copyright holders. In researching this matter, the authors compare the economic rights of creators and copyright holders in America and Indonesia through royalties and entities that manage royalties. The authors found that though music is protected under copyrights in both countries. Indonesia has a National Collective Management Institute, and America has a Mechanical Licensing Collective to collect royalties. However, the National Institute of Collective Management is not legally authorized to collect royalties from streaming platforms, and regulations in Indonesia do not determine limits for calculating the amount of royalties that creators and copyright holders can obtain. Thus, the Indonesian government must create new derivative regulations to ensure that every creator and copyright holder receives legal protection to enjoy their economic rights fully.